Faktor-Faktor yang Berhubungan dengan Kelengkapan Vaksinasi Covid-19 pada Masyarakat di Wilayah Kerja Puskesmas Kenali Besar Kota Jambi - Herastifaningsih, Shahnaz Azzahra; Guspianto, Guspianto; Syukri, Muhammad (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The Covid-19 pandemic caused by the Sars Cov-2 virus has the effect of triggering mild to severe acute respiratory tract disease with symptoms namely fever, shortness of breath, cough, fatigue, runny nose, sore throat, diarrhea, loss of the ability to smell and taste on the tongue and can cause death. Indonesia is the country with the most new cases and deaths in Southeast Asia as of 24-30 October 2022 with 19,661 new cases or 7.2 new cases per 100,000 population, even though the previous week there were 14,093 cases. This means that the addition occurred as much as 40%. This type of research is quantitative with a cross sectional design. The population of this study was all people aged > 17 years in the working area of the Puskesmas Iknew Besar, totaling 42,796 people with a sample of 172 respondents. The sampling technique used multistage random sampling. Data were collected using questionnaires and observation sheets, then univariate data analysis using the chi-square test. The results of the multivariate analysis show that there is a relationship between the completeness of the Covid-19 vaccination and attitudes, history of Covid-19, history of non-communicable diseases, perception of Covid-19 risk, family support and health information among the community in the working area of the Puskesmas Kenali Besar, Jambi City in 2022.